2017
DOI: 10.1021/acs.jpclett.7b01785
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Doping and Charge Balancing: How Polymer Acid Templates Impact the Properties of Conducting Polymer Complexes

Abstract: Polymer acids are increasingly used as dopants/counterions to access and stabilize the electrically conducting states of conducting polymers. Beyond doping and/or charge balancing, these polymer acids also serve as active components that impact the macroscopic properties of the conducting polymer complexes. Judicious selection of the polymer acid at the onset of synthesis or manipulation of the interactions between the polymer acid and the conducting polymer through processing significantly impacts the electri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 65 publications
(194 reference statements)
2
18
0
Order By: Relevance
“…In 2017, it was reported the study of a series of linear carboxylic acids whit different chain lengths of 6 trans-2-hexanoic acid carbon atoms (CA-6), trans-2-decanoic acid (CA-10), 9-tetradecanoic acid (CA-14), used as halogenfree additives-solvent, considered a sustainable and viable process useful for the production of polymeric films whit optical properties, whit potential application in solar cells. The conclusion of the study showed that increasing the length of the carboxylic acid chain changes the topology of the polymeric film [59].…”
Section: Polymermentioning
confidence: 94%
“…In 2017, it was reported the study of a series of linear carboxylic acids whit different chain lengths of 6 trans-2-hexanoic acid carbon atoms (CA-6), trans-2-decanoic acid (CA-10), 9-tetradecanoic acid (CA-14), used as halogenfree additives-solvent, considered a sustainable and viable process useful for the production of polymeric films whit optical properties, whit potential application in solar cells. The conclusion of the study showed that increasing the length of the carboxylic acid chain changes the topology of the polymeric film [59].…”
Section: Polymermentioning
confidence: 94%
“…Therefore, new absorption peaks appear at lower transition energies, in the visible and near infrared (VIS-NIR) parts of the spectrum leading to color changes (37). The electrically conducting state of conducting polymers requires delocalized charges along the conjugated backbone (38). A peculiar case is that of polyaniline where the positive charge is introduced in the π-electronic system by a proton attached on the nitrogen.…”
Section: Charge Carriers and Dopingmentioning
confidence: 99%
“…In the case of PEDOT, the conductive state is achieved by redox doping. Here, the role of the PEDOT is to carry the charge of the electrically conductive state of PEDOT (oxidized PEDOT) whereas counter ion balance the charge (38). Figure 2.9 illustrates the oxidative doping of PEDOT.…”
Section: Charge Carriers and Dopingmentioning
confidence: 99%
See 2 more Smart Citations